THE EFFECTIVENESS OF CONTENT MARKETING IN BUILDING CONSUMER TRUST: A META-ANALYSIS - Kurnia Budhy Scorita; Al-Amin (INJOSEDU: International Journal of Social and Education, 2025)
Content marketing has become an increasingly popular marketing strategy in today's digital age. However, the effectiveness of content marketing in building consumer trust is still a topic that needs to be explored further. The study in this research uses the literature method. The results show that the effectiveness of content marketing in building consumer trust and highlighting the importance of considering contextual factors in designing and implementing content marketing strategies is considered important enough that it can help marketers and brand managers in designing and implementing effective content marketing strategies to build and maintain consumer trust.